ANAUSIS NONLINIER KARAKTERISTIK DINAMIK STRUKTUR JEMBATAN CABLE-STAYED DENGAN METODA ELEMEN HINGGA - Gunawan, Iwan
Based on the aeroelastic instability calculation, the dynamic characteristic of a bridge must have certain values, especially for the first vertical bending mode and the first torsion mode. From studies carried out since, it has been seen that the torsional and bending frequencies must be sufficiently far apart to avoid flutter phenomenon. This study investigates the nonlinearity effects on static and dynamic characteristics of a long span cable-stayed bridge. Only geometric nonlinearities arise from the cable sag effect and large displacement are taken into account in this study. Case study is carried out on a long-span cable-stayed bridge of a 1000 m central span length with steel box girder and steel towers. The effect of the cable sag is emphasized here because cables play the most important role to the overall stiffness of the structures. This is shown by the lower natural frequencies as the modulus elasticity of the cables is reduced in the iteration process. Vibration mode shapes of the structure are also changed during the iteration. The natural frequencies and the mode shapes of the bridge are obtained after iteration process converged .